Transmisi Musik Lokal-Tradisional Gondang Oguong oleh Salman Azis - Habibullah, Reizki; Purwanto, Sigit; Aulia, Riza Alif (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2022)
Gondang Oguong is a local-traditional music ensemble of the community in the Limo Koto customary area of Kampar Regency. Until now, Gondang Oguong art is still being passed on to the next generation. This study aims to reveal and explain the transmission process of Gondang Oguong by artist Salman Azis, including objects, actors, and transmission mechanisms, using ethnographic methods. Salman Azis carried out the stages of the learning method, which began with efforts to attract children's interest, using close and distant communication patterns, as well as listening and imitating exercises. Transmission is one of the essential aspects of cultural inheritance related to enculturation, internalization, education, and socialization activities. For this reason, this research is expected to support the sustainable practices of local-traditional music as part of the culture.